Unexpected Affinities : Reading across Cultures - Zhang, Longxi (Book collections on Project MUSE., 2007)
"In this pioneering study, Zhang Longxi offers a much-needed reappraisal of the thematic and conceptual similarities that unite literary and cultural traditions in the East and West. An expanded version of the lectures he gave as part of the Alexander Lectures Series at the University of Toronto in 2005, Unexpected Affinities emphasizes affinity over difference and explores the relationship between East and West in terms of cultural homogeneity, challenging the traditional boundaries of cross-cultural study and comparative literature as a discipline."--Jacket